Tactile stimulation during different developmental periods modifies hippocampal BDNF and GR, affecting memory and behavior in adult rats. Issue 2 (30th December 2016) - Antoniazzi, Caren T. D.; Metz, Vinícia G.; Roversi, Karine; Freitas, Daniele L.; Vey, Luciana T.; Dias, Verônica T.; Segat, Hecson J.; Duarte, Marta M. M. F.; Burger, Marilise E.
ABSTRACT: Recent studies have shown that tactile stimulation (TS) in pups is able to prevent and/or minimize fear, anxiety behaviors, and addiction to psychostimulant drugs in adult rats. In these studies, animals have been exposed to handling from postnatal day (PND) 1–21. This study was designed to precisely establish which period of preweaning development has a greater influence of TS on neuronal development. After birth, male pups were exposed to TS from PND1–7, PND8–14, and PND15–21. In adulthood, the different periods of postnatal TS were assessed through behavioral, biochemical, and molecular assessments. Animals that received TS from PND8‐14 showed lower anxiety‐like symptoms, as observed by decreased anxiety index in elevated plus maze. This same TS period was able to improve rats' working memory by increasing the percentage of alternation rate in Y‐maze, and induce better ability to cope with stressful situations, as showed in the defensive burying test by a reduced time of burying behavior. On the other hand, animals receiving TS in the first week of life showed longest cumulative burying time, which is directly related to increased anxiety‐like behavior. Moreover, TS from PND8‐14 showed lower corticosterone levels and better oxidative status, as observed by decreased lipid peroxidation and increased catalase activity in the hippocampus. Brain‐derived neurotrophic factor (BDNF) immunocontent was increased in the hippocampus of animals receiving TS from PND8‐14, while glucocorticoid receptors immunocontent was decreased in both TS1‐7 and TS15‐21, but not TS8‐14 . To the best of our knowledge, this study is the first to show TS can be more efficient if applied over a focused period of neonatal development (PND8‐14) and this beneficial influence can be reflected on reduced emotionality and increased ability to address stressful situations in adulthood. © 2016 Wiley Periodicals, Inc.